Multitransmission Zero Dual-Band Bandpass Filter Using Nonresonating Node for 5G Millimetre-Wave Application. (13th December 2018) - Shi, Liyun; Gao, Jianjun
Abstract : A planer millimetre-wave dual-band bandpass filter with multitransmission zeros is proposed for 5G application. This filter includes two dual-mode open-loop resonators. The U-shape nonresonating node is employed to generate an extra coupling path. Finally, a dual-band bandpass filter with five transmission zeros is obtained. The filter is fabricated and measured. Good agreement between simulation and measurement is obtained.